A Practical Approach to Spine Imaging. Issue 1 (February 2015) - Klein, Joshua P.
Abstract : Purpose of Review: : The spine is a complex mechanical structure that surrounds and protects the spinal cord and nerve roots. It is capable of multidirectional movement and is susceptible to a large variety of pathologies that can affect spinal cord and nerve root function. Detection of spinal pathology is aided by a familiarity with normal spinal anatomy and its appearance on CT and MRI studies. Imaging of the spine is performed frequently, and a systematic approach toward image interpretation can prevent overlooking or incompletely assessing a lesion. Recent Findings: : CT and MRI of the spine provide detailed views of normal and abnormal structures and allow for differentiation of vascular, inflammatory, infectious, neoplastic, traumatic, and degenerative etiologies of spine disease. Summary: : This article provides a strategy for interpreting CT and MRI studies of the spine and can be used as a primer for the other articles that follow in this issue ofCONTINUUM, in which specific etiologies of spine and spinal cord pathology are considered in detail.